Disaster Socialization and Assistance as an Effort for Post-Disaster Social and Environmental Recovery in Mendale Village, Kebayakan District, Aceh Tengah - Amri Amri; zulkifli zulkifli; ihsan Ihsan; Sayuti Sayuti; Junia Farma; Arya Gusmana (Jurnal Pengabdian Bakti Akademisi, 2026)
The flash flood and landslide disaster in Mendale Village, Kebayakan District, Central Aceh caused environmental damage and social and psychological impacts on the community, especially vulnerable groups. The main post-disaster problems were limited understanding of the disaster, limited structured environmental recovery, and minimal ongoing psychosocial assistance. This community service activity aims to accelerate social and environmental recovery through community-participation-based disaster socialisation. The method used was a Service Learning approach with four stages: planning, socialisation, implementation, and evaluation. The activity involved approximately 40 participants, including village officials, community leaders, youth, housewives, and schoolchildren. The program included socialisation of disaster mitigation and preparedness, community service cleaning public facilities, psychosocial assistance for children through educational games and storytelling, and strengthening environmental resilience through planting family medicinal plants and vegetables in the village office area. Data were collected through observation, pre-tests, post-tests, and interviews. The results of the activity showed a significant increase in community understanding of disasters from low to good and very good. Furthermore, the village environment became cleaner and more functional, community participation in community service activities increased, and children's anxiety symptoms decreased through trauma healing activities. These activities also fostered a collective community commitment to maintaining environmental cleanliness and independently implementing disaster preparedness principles. These findings demonstrate that participatory disaster awareness campaigns are effective as a post-disaster social and environmental recovery strategy in disaster-prone rural areas.